Nanohybrids: A Burgeoning Need to Cater C−C and C−O Bonds Building in Organic Synthesis - Gupta, Nikita; Anku, Kumar; Singh, Anurag; Routray, Sampurna; Kar, Ankita; Kumar Das, Vijay (ChemistrySelect (Weinheim), 2023)
Nanohybrids (NHs) based on the conjugation of multiple carbonaceous nanomaterials and metal/metal oxides, are emerging as important photocatalysts of 21st century and have tremendous future scopes. Overcoating one material on top of another in NHs improves performance and multifunctionality growth for a wide range of catalytic applications in organic transformations. The catalytic activity of NHs brings a phenomenal change towards various organic synthetic reactions to improve their selectivity, productivity and yield. Thus, with the background of this context, the current review covers the state of art literature up to July 2022 and brings a comprehensive discussion on the entitled subject matter. As emphasized in this review, the application of heterogeneous NHs for common organic reactions has been confirmed to be a successful tactic for the growth of extremely resourceful conversions in terms of atom economy, atom efficiency E‐factor and selectivity. It also highlights the extensive and critical aspects to explore the catalytic prospects and challenges of NHs from obscurity to eminence. For the efficient effective and promising catalysis of a wide range of organic transformations under environmental favourable conditions, there is a rising demand for highly sustainable nanohybrids. The nanohybrids can be used as an appropriate photocatalyst to enhance the selectivity and productivity of chemical reactions. The current review delves into the potential application of multifaceted nanohybrids for the synthesis of significant organic compounds.